Mengonsep Sintesis Sains Dan Al-Qur’an (SSQ) Sebagai Teknik Pengintegrasian Ilmu Ekonomi Melalui Pendekatan Maqashid Syariah (Studi Analisis Konten) - Yusuf, Sitti Rabiah (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to conceptualize the synthesis of science and the Koran as a strategy to integrate economics with the Koran. The research method uses content analysis on the research objects of Management Accounting books and synthetic thinking books. The results of this research show that 1) The synthesis of science and the Qur'an is carried out by combining economic messages contained in management accounting books with economic sentences in the Qur'an. Like the science of ushul fiqh which uses sentence fragments in verses of the Koran as a basis for study in determining Islamic economic law. 2) the Management Accounting book by Mulyadi contains elements of maqasid sharia in the form of reason and assets which are characterized by the presence of concrete sentences in the form of thoughts (reason) and the use of numbers.